Safe spaces: Exploration of the transformative power of online graduate programs for adult learners - Patricia J Higgins (Adult Education Research Conference, 2024)
The purpose of this exploratory case study was to consider how instructors can facilitate a safe and inclusive environment for adult learners in an online graduate program and to explore the potential benefits of such a learning space. Through a thematic analysis of the case study materials, three prominent themes emerged. The three themes were: a) seeking to engage through sharing life experiences, b) mindfulness-based reflective practice, and c) facilitating safe and inclusive spaces as a path to transformation. This study adds to current literature by validating the importance of creating a safe and inclusive environment for adult learners in distance education programs. This study also provides guidance for adult educators who teach online, recommending meaningful ways to integrate adult learning theory into instructional practices in order to promote students’ sense of belonging, engagement, and persistence.
Keywords: distance adult education; intersectionality; instructional methods